Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/exd.13845
|View full text |Cite
|
Sign up to set email alerts
|

Sirt5 is dispensable for BrafV600E‐mediated cutaneous melanoma development and growth in vivo

Abstract: Sirt5 is known to functionally regulate mitochondrial proteins by altering posttranslational modifications, including lysine desuccinylation. While roles for Sirt5 as either a tumor promoter or suppressor, or in chemoresistance, have been implicated in other cancers, the function of Sirt5 in cutaneous melanoma has not been well examined. Therefore, to determine whether Sirt5 is necessary for BrafV600E‐mediated melanoma formation and/or disease progression, we crossed a genetically engineered murine melanoma mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In contrast, SIRT5 was found to inhibit gastric cancer cell proliferation and tumor formation by inhibiting aerobic glycolysis (36). Interestingly, SIRT5 is not necessary for BrafV600E-mediated cutaneous melanoma initiation and growth in vivo (37). With respect to its function in chemoresistance, SIRT5 knockdown sensitizes NSCLC A549 cells to multiple chemotherapeutics including cisplatin (13).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, SIRT5 was found to inhibit gastric cancer cell proliferation and tumor formation by inhibiting aerobic glycolysis (36). Interestingly, SIRT5 is not necessary for BrafV600E-mediated cutaneous melanoma initiation and growth in vivo (37). With respect to its function in chemoresistance, SIRT5 knockdown sensitizes NSCLC A549 cells to multiple chemotherapeutics including cisplatin (13).…”
Section: Discussionmentioning
confidence: 99%
“…[59] In contrast to SIRT6, sirtuin 5 (SIRT5) does not improve sensitivity to BRAF inhibitors in BRAF V600 -mutant melanoma animals. [59,60] Given the targetable properties of SIRT6 in melanoma and non-melanoma skin cancers, the development of SIRT6-specific inhibitors accompanied by detailed molecular insights into the mechanistic and therapeutic tangibility of SIRT6 in skin is essential for the development of novel strategies to modulate skin cancer. [59]…”
Section: S Irt6 In Mel Anoma and Non -Mel Anoma S Kin C An Cer Smentioning
confidence: 99%
“…This study identified not only an epigenetic mechanism of drug resistance, but also provided a rationale for a new combination therapy that could overcome resistance to standard‐of‐care therapy for BRAF V600 ‐mutant melanoma patients . In contrast to SIRT6, sirtuin 5 (SIRT5) does not improve sensitivity to BRAF inhibitors in BRAF V600 ‐mutant melanoma animals . Given the targetable properties of SIRT6 in melanoma and non‐melanoma skin cancers, the development of SIRT6‐specific inhibitors accompanied by detailed molecular insights into the mechanistic and therapeutic tangibility of SIRT6 in skin is essential for the development of novel strategies to modulate skin cancer …”
Section: Sirt6 In Melanoma and Non‐melanoma Skin Cancersmentioning
confidence: 99%
“…The role of SIRT4 and SIRT7 in melanoma have not been explored. SIRT5 has been shown to be dispensable for BRAF V600E -mediated melanoma development and also does not affect sensitivity to a selective BRAF inhibitor (16). Similar to SIRT1 and SIRT3, SIRT6 has been shown to possess a pro-proliferative role in melanoma (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%